Association Between Postdischarge Emergency Department Visitation and Readmission Rates. Issue 9 (15th March 2018) - Venkatesh, Arjun K.; Wang, Changqin; Wang, Yongfei; Altaf, Faseeha; Bernheim, Susannah M.; Horwitz, Leora
Abstract : BACKGROUND: Hospital readmission rates are publicly reported by the Centers for Medicare & Medicaid Services (CMS); however, the implications of emergency department (ED) visits following hospital discharge on readmissions are uncertain. We describe the frequency, diagnoses, and hospital‐level variation in ED visitation following hospital discharge, including the relationship between risk‐standardized ED visitation and readmission rates. METHODS: This is a cross‐sectional analysis of Medicare beneficiaries hospitalized for acute myocardial infarction (AMI), heart failure, and pneumonia between July 2011 and June 2012. We used Medicare Standard Analytic Files to identify admissions, readmissions, and ED visits consistent with CMS measures. Postdischarge ED visits were defined as treat‐and‐discharge ED services within 30 days of hospitalization without readmission. We utilized hierarchical generalized linear models to calculate hospital risk–standardized postdischarge ED visit rates and readmission rates. RESULTS: We included 157, 035 patients hospitalized at 1, 656 hospitals for AMI, 391, 209 at 3, 044 hospitals for heart failure, and 342, 376 at 3, 484 hospitals for pneumonia. After hospitalization for AMI, heart failure, and pneumonia, there were 14, 714 (9%), 31, 621 (8%), and 26, 681 (8%) ED visits, respectively. Hospital‐level variation in postdischarge ED visit rates was substantial: AMI (median: 8.3%; 5th and 95th percentile: 2.8%‐14.3%), heart failure (median: 7.3%; 5th and 95th percentile: 3.0%‐13.3%), and pneumonia (median: 7.1%; 5th and 95th percentile: 2.4%‐13.2%). There was statistically significant inverse correlation between postdischarge ED visit rates and readmission rates: AMI (–0.23), heart failure (‐0.29), and pneumonia (–0.18). CONCLUSIONS: Following hospital discharge, ED treat‐ and‐discharge visits are half as common as readmissions for Medicare beneficiaries. There is wide hospital‐level variation in postdischarge ED visitation, and hospitals with higher ED visitation rates demonstrated lower readmission rates.